2020
DOI: 10.1038/s41467-020-14700-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting WNT and NOTCH in renal cancer stem cells and the implications for human patients

Abstract: Current treatments for clear cell renal cell cancer (ccRCC) are insufficient because two-thirds of patients with metastases progress within two years. Here we report the identification and characterization of a cancer stem cell (CSC) population in ccRCC. CSCs are quantitatively correlated with tumor aggressiveness and metastasis. Transcriptional profiling and single cell sequencing reveal that these CSCs exhibit an activation of WNT and NOTCH signaling. A significant obstacle to the development of rational tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 69 publications
5
115
0
Order By: Relevance
“…Since organoids closely recapitulate several properties of the original tumor and since they are scalable for high-throughput drug screens, they present excellent in vitro systems that connect clinical trials with cancer genetics, complement current preclinical model-based drug studies and advance the development of personalized therapy design. This has been successfully demonstrated in colorectal cancer organoids as well as in our study on kidney cancer organoids 5,11 .…”
Section: Applications and Limitations Of The Protocolsupporting
confidence: 56%
See 4 more Smart Citations
“…Since organoids closely recapitulate several properties of the original tumor and since they are scalable for high-throughput drug screens, they present excellent in vitro systems that connect clinical trials with cancer genetics, complement current preclinical model-based drug studies and advance the development of personalized therapy design. This has been successfully demonstrated in colorectal cancer organoids as well as in our study on kidney cancer organoids 5,11 .…”
Section: Applications and Limitations Of The Protocolsupporting
confidence: 56%
“…We have shown that organoids exhibit kidney-specific epithelial differentiation, while retaining cancer stem cell populations. Organoids resemble proximal tubule structures -the potential cell of origin of ccRCC -and recapitulate typical characteristics of ccRCC, including glycogen deposits and lipid droplets 5 .…”
Section: Comparison With Other Methodsmentioning
confidence: 69%
See 3 more Smart Citations